1H NMR kinetic investigation of the equilibrium between the Z- and E- isomers in a stable phosphorus ylide involving 2-mercaptobenzimidazole. (1st September 2013) - Khorassani, Sayyed Mostafa Habibi; Maghsoodlou, Malek Taher; Ebrahimi, Ali; Kazemian, Mohammad Amin; Salari, Sara Sameh; Nasiri, Shahin
A kinetic investigation of the interchange process in the equilibrium between the Z- and E- isomers of a stable phosphorus ylide involving 2-mercaptobenzimidazole has been undertaken by the 1H NMR technique. Kinetic and activation parameters such as k–1, k1, ktotal, Ea1, Ea–1, Eatotal, ΔS#, ΔH# and ΔG# along with the thermodynamic parameters Ke, ΔH°, ΔG° and ΔS° were obtained from the experimental data for the forward and reverse reactions.